2019
DOI: 10.4274/turkderm.galenos.2019.97355
|View full text |Cite
|
Sign up to set email alerts
|

Riga-Fede disease like ulcers in old age: A case report

Abstract: Riga-Fede disease (RFD) is a traumatic, reactive benign disorder characterized by persistent ulceration on the tip or ventral surface of the tongue, seen mainly in infants and children. Lesions tend to develop after the eruption of natal or primary incisors, resulting from repetitive traumatic damage due to backward and forward movements of the tongue over the lower incisors. A literature survey has revealed a very limited number of reported cases of RFD in adults. Herein we reported a 70-year-old female patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 7 publications
0
0
0
Order By: Relevance
“…this condition has been known by a number of different names, including Riga's disease, Riga-Fede disease or syndrome, sublingual granuloma, and traumatic sublingual ulceration [3]. A "PubMed" research revealed only 61 published cases of RFD in infants and children till now [4].…”
Section: Case Reportmentioning
confidence: 99%
“…this condition has been known by a number of different names, including Riga's disease, Riga-Fede disease or syndrome, sublingual granuloma, and traumatic sublingual ulceration [3]. A "PubMed" research revealed only 61 published cases of RFD in infants and children till now [4].…”
Section: Case Reportmentioning
confidence: 99%